Investigation of quality, safety and composition of biologically active substances of vitamin and mineral feed concentrate - R. V. Kazaryan; A. S. Borodikhin; A. A. Fabritskaya; A. N. Matvienko; M. V. Lukyanenko (Новые технологии)
The aim of the experiment is to study the quality, safety and composition of biologically active substances contained in vitamin-mineral feed concentrate.